Humanization of the Technological Environment as a Vector of Social Responsibility of Business - M. A. Izmailova (Модернизация, инновация, развитие, 2020)
Purpose: the main goal of the research is to develop a humanistic approach to digital transformation management based on the principles of social responsibility in the current uncertain environment.Methods: the research is based on the integration of conceptual approaches to understanding the specifics of the functioning of a modern organization in the context of digital transformation and the impact of the new crisis on Russian business. The author attempts to determine the emerging trends in the impact of the coronavirus pandemic on the decisions made by company managers in relation to their employees. The basic concepts of the research cover the areas of digitalization of the economy, humanization of economic growth, human capital, personnel management, and social responsibility of business.Results: the analysis of the combined influence of factors of economic, technological, demographic and cultural Genesis on the formation of a new approach to the construction of interaction between organizations and people in the direction of greater emphasis on anthropocentrism. It is determined that this kind of relationship should be based on the principles of socially responsible business behavior, recognizing the person as the main resource for digital transformation, achieving commercial success and sustainable development. The article assesses the real situation in the labor market and in Russian companies under the influence of digital challenges and the coronavirus pandemic. It is emphasized that the demand for social orientation of business increases many times during crisis periods, during which there is a rethinking of values and the formation of new foundations for future development. Recommendations are given for eliminating or minimizing the conflict between humanistic and technocratic approaches in the management of companies based on the principles of social responsibility.Conclusions and Relevance: the solution of a set of tasks for the digital transformation of the economy, saturating the business environment with new technological solutions, in the current conditions of uncertainty formed under the influence of the coronavirus pandemic, actualizes the problem of preserving humanity in a technologizing world. It is imperative to find ways to remove the generally accepted (perhaps far-fetched?) contradictions between human essence and technological transformations. Companies, while adopting strategic guidelines in the field of goal setting, building their potential and building prospects, should give priority to the development of human resources as an integral element of technological progress and a key factor in creating long-term value for companies and society as a whole.